2015
DOI: 10.1038/eye.2015.202
|View full text |Cite
|
Sign up to set email alerts
|

Depth evaluation of intended vs actual intacs intrastromal ring segments using optical coherence tomography

Abstract: Purpose Evaluation of actual vs intended intrastromal corneal ring segments (ICRS) implantation depth as measured by anterior segment optical coherence tomography (OCT) Methods Prospective study evaluating 30 Intacs segments implanted manually in 19 eyes of 15 patients suffering from keratoconus. Segment depth evaluation was performed using anterior segment OCT. Measurements were performed above and below the segment at 3 points in relation to the incision site. Statistical analysis was performed using the SAS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 19 publications
2
13
0
1
Order By: Relevance
“…Most of the previous studies 9, 10,12,14 published about this subject report on the use of Intacs ICRS and do not Predictability of ICRS Tunnel Depth/Monteiro et al compare both techniques. Barbara et al 10 studied with OCT the depth of implantation of Intacs ICRS after manual surgery.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most of the previous studies 9, 10,12,14 published about this subject report on the use of Intacs ICRS and do not Predictability of ICRS Tunnel Depth/Monteiro et al compare both techniques. Barbara et al 10 studied with OCT the depth of implantation of Intacs ICRS after manual surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the previous studies 9, 10,12,14 published about this subject report on the use of Intacs ICRS and do not Predictability of ICRS Tunnel Depth/Monteiro et al compare both techniques. Barbara et al 10 studied with OCT the depth of implantation of Intacs ICRS after manual surgery. Our results, with a larger sample, confirm those reported in this previous study, in which the authors found a shallower than planned intrastromal tunnel performed by mechanical dissection (308 µm instead of the expected 461 µm; P < .05).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ring segments can also be inserted deep into the corneal stroma to correct corneal curvature in keratoconus. AS‐OCT can determine the position of the ring segments during implantation, and prevent unwanted complications, including anterior chamber perforation or epithelial‐stromal breakdown …”
Section: Resultsmentioning
confidence: 99%
“…In order to avoid complications associated with shallow segment implantation, aiming for an implantation depth of 70% total corneal thickness is common practice [ 12 , 13 ]. Using three points above and below the implantation site, we calculated the average depth of our patient’s INTACS segment to be 75.08% total corneal thickness [ 13 ]. It is unclear if this depth was part of the surgical plan or if it was due to posterior migration of the implant.…”
Section: Discussionmentioning
confidence: 99%